A novel mining system for criminal issues from a video file within cloud computing environment - Ibbini, Emad Mohammed; Ibbini, Mohammed Salameh; Kweh, Yeah Lun (IJENS Publisher, 2014)
This paper presents a description of a novel mining system which mines the different occurrences (instances) of the same object from a video file. The framework of the system consists of four steps: segmenting the video file into stable tracks, extracting objects and their features from the tracks, grouping these tracks into clusters based on their residing objects, and finally mining the instances of each object in the shared pool of configurable computing resources within cloud environment for more security. The paper also presents a critique and feedback for the system and proposes an idea to improve its performance.